Elevation dependency of ecosystem services supply efficiency in great lake watershed. (15th September 2022) - Jiang, Song; Cheng, Xueyan; Yu, Shuying; Zhang, Hanbing; Xu, Zihan; Peng, Jian
Abstract: Although it is well acknowledged that the improvement of ecosystem services is conducive to human well-being, there is still a lack of approach to determining reasonable improvement goals, especially for ecosystem services with trade-off relationship. Based on the method of production possibility frontier (PPF), this study presented a novel approach to identifying the improvement goals of interacting ecosystem services with considering their context dependency. By calculating the gap between the current supply of ecosystem services and the reasonable improvement goal, the ecosystem services supply efficiency was defined and measured to identify the optimization potentials of ecosystem services with trade-off relationship. The results showed that the supply efficiency of ecosystem services (grain production and water purification) decreased and then increased significantly along with the increasing of farmland area ratio in the Dongting Lake Basin (DLB). Meanwhile, the inflection point appeared when the farmland area ratio was 0.16. The change of farmland area ratio was significantly influenced by the change of elevation, with the regression coefficients of elevation on the left and right sides of the inflection point being −1.28 and −0.5 respectively, which were higher than that of other factors. Along with the increasing of elevation, the ecosystem services supply efficiency decreased but increased when the elevation exceeded 721.74 m. Furthermore, the sub-watersheds with farmland area ratio below the inflection point, i.e. mainly high elevation areas, were located around national or provincial level poor counties, posing a great challenge for improving ecosystem services with trade-off relationship. Development strategies for sub-watersheds should consider the non-linear trade-offs of ecosystem services, especially the opposite stages of supply efficiency. This study highlighted the elevation dependency of ecosystem services supply efficiency through farmland area ratio in great lake watershed. Graphical abstract: Image 1 Highlights: Production possibilities frontier was used to identify improvement goals of ecosystem services. Ecosystem services supply efficiency was defined to quantify the optimization potential of ecosystem services. Ecosystem services supply efficiency showed two opposite stages of responses to farmland area ratio. The two opposite responses were both dominated by elevation through farmland area ratio.